Probable Person-to-Person Transmission of Avian Influenza A (H5N1) - Ungchusak, Kumnuan; Auewarakul, Prasert; Dowell, Scott F; Kitphati, Rungrueng; Auwanit, Wattana; Puthavathana, Pilaipan; Uiprasertkul, Mongkol; Boonnak, Kobporn; Pittayawonganon, Chakrarat; Cox, Nancy J; Zaki, Sherif R; Thawatsupha, Pranee; et al. (The New England journal of medicine, 2005)
This investigation was conducted in Thailand after a young girl and her mother died from acute viral pneumonia and an aunt with whom the girl had lived also had severe viral pneumonia. Samples from the mother and aunt were positive for avian influenza (H5N1) infection. In this cluster of avian influenza infection, two of the patients had had no exposure to ill birds, suggesting that person-to-person transmission occurred. During the first months of 2004, outbreaks of highly pathogenic avian influenza caused by influenza A (H5N1) virus were recognized in eight Asian countries. 1 , 2 The poultry outbreaks receded and then reappeared in July in five countries, with human cases recognized in Vietnam and Thailand. 3 As of November 11, 2004, there had been 44 documented human infections and 32 deaths (mortality, 73 percent), sparking fears that this lethal pathogen might cause a pandemic. Since the first avian influenza outbreak, in 1997, 4 there has been concern that the influenza A (H5N1) virus might either mutate and adapt to allow efficient transmission . . .